Effect of Metakaolin on the Diffusion Properties of Chloride Ions in Cement Mortar under the Coupling Effect of Multiple Factors in Marine Environment - Yezhen Yuan; Kaimin Niu; Bo Tian; Lijuan Kong; Lihui Li (Advances in Civil Engineering)
To address the problem of chloride ion transport in cement concrete in marine environment, this study investigates the effect of metakaolin dosage on the chloride ion diffusion resistance of mortar and its mechanism by testing the chloride ion binding capacity and microstructure of mortar under the coupling effect of chlorine salt-sulfate-carbonation multiple factors. The results show that the coupling of sulfate or carbonation reduces chloride ion transport to some extent compared with single chlorine salt attack, while the three-factor coupled environment promotes free chloride ion diffusion. This is because the products of calcium alumina, gypsum, and calcium carbonate grow together and compete with each other to form more large capillaries; thus, accelerating the diffusion of chloride ions in cement mortar. Metakaolin, due to its higher pozzolanic activity, increases the monocarbon aluminate content in the erosion products, promotes F-salt generation, and increases the Al/Si ratio, which strengthens the binding ability of C-S-H gel to chloride ions, so the free chloride ion concentration inside the specimens doped with metakaolin is lower. In particular, the three-factor coupled environment has less 0.05–10 μm capillary pore content and higher F-salt stability in the specimens, which has the strongest effect on chloride ion curing, and the free chloride ion concentration integral in M-SCCl is reduced by nearly 30% compared with MF-SCCl and F-SCCl.